1991
DOI: 10.1121/1.2029833
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of locus equations as a source of relational invariance for stop place categorization

Abstract: Locus equations were investigated as a potential higher-order metric capable of illustrating relational invariance for place of articulation in voiced initial stop consonants independently of vowel context. Locus equations are straight-line regression fits to data points formed by plotting onsets of F2 transitions along the y axis and their corresponding midvowel nuclei along the x axis. Twenty subjects, 10 male and 10 female, produced /b/v/t/, /d/v/t/, and /g/v/t/ tokens for 10 vowel contexts. Each CVC token … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 0 publications
5
93
1
Order By: Relevance
“…It is almost certainly the case that there are regularities in acoustics that result from coarticulation (see, e.g., Sussman, McCaffrey, & Matthews, 1991) and that listeners are sensitive to these regularities in speech perception (Holt, Lotto, & Kluender, 1998;Nearey, 1997;Smits, 2001). Nevertheless, spectral contrast may play a supporting role even in these cases.…”
Section: Criticism 3: Spectral Contrast Results In a Loss Of Sensitivmentioning
confidence: 94%
“…It is almost certainly the case that there are regularities in acoustics that result from coarticulation (see, e.g., Sussman, McCaffrey, & Matthews, 1991) and that listeners are sensitive to these regularities in speech perception (Holt, Lotto, & Kluender, 1998;Nearey, 1997;Smits, 2001). Nevertheless, spectral contrast may play a supporting role even in these cases.…”
Section: Criticism 3: Spectral Contrast Results In a Loss Of Sensitivmentioning
confidence: 94%
“…To the extent that patterns of covariance among acoustic attributes in natural sounds are efficiently coded, these non-isomorphic representations may inform how the auditory system exploits different patterns of redundancy to learn to distinguish different speech sounds. For example, extraction of relational properties across variations consequent to coarticulation (e.g., locus equations, Sussman et al, 1991Sussman et al, , 1998 or anatomy (scaling of formant frequencies across changes in vocal tract length across talkers, Kluender et al, 2011) are the most direct speech analogs to non-isomorphism demonstrated here. In related studies employing fMRI, Okada et al (2010) report that responses in bilateral posterior superior temporal sulcus were sensitive to phonemic variability (intelligibility) of speech sounds, but not to acoustic variability.…”
Section: Discussionmentioning
confidence: 99%
“…While the novel sounds employed here varied only along three acoustic dimensions (one of which varied randomly), patterns of covariance naturally scale to high-dimensional feature spaces. In complex natural stimuli such as speech, multiple forms of stimulus attribute redundancy exist concurrently and successively (e.g., Delattre et al, 1955;Kluender et al, 2011;Lisker, 1978;Repp, 1982;Sussman et al, 1991Sussman et al, , 1998. To the extent that patterns of covariance among acoustic attributes in natural sounds are efficiently coded, these non-isomorphic representations may inform how the auditory system exploits different patterns of redundancy to learn to distinguish different speech sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Production of every consonant and vowel overlaps in time (and in the vocal tract) with speech sounds that precede and follow. In addition, acoustic characteristics within vowels provide rich evidence concerning neighboring consonants and vice versa (8)(9)(10)(11).…”
mentioning
confidence: 99%